2004
DOI: 10.1111/j.1365-2672.2004.02270.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of Gluconobacter oxydans and Bacillus megaterium in a two-step process of l-ascorbic acid manufacture by ion beam

Abstract: Aim: To increase the transformation rate of L L-sorbose to 2-keto-L L-gulonic (2-KLG) acid in a two-step process of L L-ascrobic acid manufacture by ion beam. Methods and Results: Gluconobacter oxydans (GO29) and Bacillus megaterium (BM80) were used in the present study. Ion implantation was carried out with the heavy ion implantation facility at the institute of Plasma Physics in China. 2-KLG in whole culture broth was determined by iodometry. Mutants were screened by singlecolony isolation and 2-KLG accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 15 publications
0
40
1
1
Order By: Relevance
“…, He ? , and it was the most common ion used in ion beam implantation [13]. For ion implantation, mutation frequency and screen efficiency are closely related to the energy and the doses of ions [14].…”
Section: Effect Of Nmentioning
confidence: 99%
“…, He ? , and it was the most common ion used in ion beam implantation [13]. For ion implantation, mutation frequency and screen efficiency are closely related to the energy and the doses of ions [14].…”
Section: Effect Of Nmentioning
confidence: 99%
“…Studies have showed that both internal and external metabolites from B. megaterium , through biochemical and molecular methods and certain proteins or amino acids, play a role in this process Zhao et al 2008 ) . Further research has shown that B. megaterium secretes two kinds of proteins of about 30-50 kDa and >100 kDa that improve K. vulgare growth and increase 2-KLG productivity (Lu et al 2003 ;Xu et al 2004 ;Zhao et al 2008 ) . However, researchers have not speci fi cally determined which proteins play a role in promoting K. vulgare growth and 2-KLG production.…”
Section: Effects Of the Relationship Between Two Bacteria In Mixed Cumentioning
confidence: 97%
“…In another process, D -glucose was converted to 2,5 -diketo -D -gluconic acid by Erwinia or Acetobacter which was then transformed into 2 -KLGA by Corynebacterium [99] . Another similar process involved mutants of G. oxydans and Bacillus megaterium [100] . A genetically engineered strain of Erwinia herbicola produced 120 g/l of 2 -KLGA [101], whereas recombinant G. oxydans made 130 g/l [102] .…”
Section: Vitaminsmentioning
confidence: 99%